A Systematic Review of the Nexus between Teacher Feedback and Student Motivation - Badrun Badrun (Penelitian dan Pengembangan Ilmu, 2024)
The link between teacher feedback and student motivation is an important aspect in educational research, influencing students' academic performance and their learning experiences. This systematic literature review investigates the role of self-assessment and peer-assessment in strengthening the relationship between teacher feedback and student motivation. Through a comprehensive analysis of existing literature, this study explores how these factors interact to increase the effectiveness of teacher feedback in stimulating student motivation. Findings highlight the importance of integrating self-assessment and peer-assessment practices into educational contexts to optimize student engagement and achievement. Implications for practice and future research directions are discussed.